Coagel Prepared from Aqueous Octyl β‐d‐Galactoside Solution. Issue 1 (2nd November 2016) - Ogawa, Shigesaburo; Koga, Maito; Asakura, Kouichi; Takahashi, Isao; Osanai, Shuichi
Abstract: Structuring of semi‐crystalline networks in water systems is significant for a variety of industrial applications. In the present work, we investigated the coagel formation from aqueous octyl β ‐d ‐galactoside (C8 ‐ β ‐Gal) solutions and characterized the crystal structure and crystallite network in the prepared coagel. Differential scanning calorimetry (DSC) confirmed that the Krafft boundary temperature ( T K ) is 32–35 °C for C8 ‐ β ‐Gal concentrations below 30 wt% and a knee of the Krafft boundary exists around 2.5 wt% C8 ‐ β ‐Gal concentrations. The addition of NaCl increased T K slightly because of the salting‐out effect. Powder X‐ray diffraction (PXRD) analysis, field‐emission scanning electron microscopy (FE‐SEM) and atomic force microscopy (AFM) observations revealed that the coagel is comprised of the three dimensional bundled semi‐crystalline network consisting of a "ribbon crystal phase" of hemihydrate crystals. Moreover, the excellent ability of C8 ‐ β ‐Gal to form a macroscopically homogeneous coagel was demonstrated by the comparison with other representative mono‐alkylated glycoside' systems containing octyl a ‐d ‐glucoside or dodecyl β ‐d ‐glucoside. Persistence of the liquid phase without liquid–liquid phase separation prior to and during the coagel formation was a key factor for the preparation. A novel coagel was obtained from a principal synthetic galactoside.